Corporate Governance and Sustainable Energy Performance: Challenges and Strategies of Moroccan Subsidiaries in the Green Transition - Taghzouti, Hamza; Taghzouti, Abdellatif (International Journal of Energy Economics and Policy, 2025)
In the current global landscape shaped by the energy transition and increasing sustainability imperatives, corporate governance is progressively recognized as a strategic driver for enhancing energy responsibility. This study investigates the influence of governance mechanisms on energy performance and sustainability within subsidiaries of Moroccan business groups. Adopting a quantitative and deductive research design, the study develops a conceptual framework that links governance quality, energy transparency, and sustainable performance. Empirical data were collected from a sample of subsidiaries operating in energy-intensive industries. Multiple linear regression analysis was employed to test the hypotheses derived from prior research on corporate governance and sustainability. The results reveal a positive and statistically significant relationship between governance mechanisms and energy responsibility, demonstrating that transparency, strategic oversight, and board commitment contribute to improved sustainable performance among subsidiaries. These findings confirm that corporate governance plays a pivotal role in supporting Morocco’s energy transition. They further underscore the necessity of adopting governance frameworks that explicitly integrate energy responsibility into strategic and operational decision-making. This research enriches the literature on energy governance in emerging economies by proposing an integrated empirical model of sustainable performance contextualized to Moroccan corporate realities.